Photomechanical B←N Molecular Crystals: From Single-Crystal-to-Single-Crystal [2 + 2] Photodimerization to Polymerization - Bhandary, Subhrajyoti; Shukla, Rahul; Kaczmarek, Anna M.; Van Hecke, Kristof (Accounts of chemical research, 2025)
Conspectus Organoboron-based crystalline compounds, which can respond to external stimuli (heat, light, electric field, or pressure), have already emerged as smart materials with well-directed functions. While various weak noncovalent interactions remain key to the supramolecular design, the exploitation of relatively strong boron–nitrogen dative bonds (B←N bonds) in constructing functional crystalline molecular and polymeric assemblies has recently attracted significant research interest. In particular, the strategic incorporation of B←N bonds into stimuli-responsive crystalline materials is promptly shaping a new direction in the field. Photomechanical or photodynamic crystals are a special kind of stimuli-sensitive smart material that can undergo rapid dynamic motions (jumping, bending, splitting, or curling) when exposed to UV/visible light. These instantaneous macroscopic crystal movements promoted by the used light source are collectively known as “photosalient effects”. Metal-free/organic molecular crystals, exhibiting photosalient effects, provide an efficient choice of material to transform photon energy into mechanical work owing to their inherent lightweight, noncovalently bonded, and defectless packing. Therefore, such dynamic crystals are extremely relevant as an alternative to sustainable and flexible materials for soft robotics, actuators, energy storage, and sensors. These photodynamic crystal motions or photosalient effects can be induced by topochemical [2 + 2] cycloaddition reactions, mostly under high-energy UV light, as has recently been observed. In contrast, photodynamic motions triggered by visible light or even solar energy are less frequently encountered. However, topochemical [2 + 2] photoreactions do not always guarantee the exhibition of mechanical motions in crystals. While topochemical [2 + 2] photoreactivity has long been a subject of investigation, the study of photomechanical crystalline materials has only recently emerged as a key research focus. Following the pioneering work of Schmidt ( Schmidt, G. M. J. Pure Appl. Chem. 1971, 27, 647−678 10.1351/pac197127040647 ), the topochemical [2 + 2] photodimerization reaction of olefins has arisen as a promising route to obtain novel crystalline materials with a wide variety of topologies and unique properties based on small organic molecules, discrete metal complexes, metal-coordination polymers, and organic polymers, which are otherwise not achievable by solution-phase synthesis. When any topochemical transformation proceeds to “completion” in a single-crystal-to-single-crystal (SCSC) manner, it carries invaluable structural and mechanistic information related to the crystal properties. In all these compounds, weak supramolecular interactions (hydrogen/halogen/​chalcogen bonds or stacking interactions) and robust metal-coordinate bonds have been observed to direct [2 + 2] topochemical reactivity within the principle of crystal engineering. On the contrary, the organization of organoboron molecules in crystals, exhibiting photomechanical effects and solid-state reactions directed by B←N dative bonds, is seldom reported. Also, supramolecular B←N force-supported topochemical synthesis of crystalline organoboron polymers has yet to be explored. This Account summarizes our recent research progress on the design and development of molecular B←N bonded crystalline adducts that exhibit UV-to-visible light-induced macroscopic mechanical motions, accompanied by SCSC topochemical [2 + 2] dimerizations to polymerizations. We provide challenges and opportunities for future developments of B←N bond-directed photoresponsive crystalline materials within the context of crystal engineering, materials science, and organoboron chemistry. In brief, our work contributes to the rational design of efficiently energy-transducing photomechanical crystals based on molecular organoboron compounds, which undergo SCSC [2 + 2] photocycloaddition reactions to form novel molecular and polymeric crystalline materials.